2012
DOI: 10.1007/s11524-011-9662-6
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging of Xylazine as a New Drug of Abuse and its Health Consequences among Drug Users in Puerto Rico

Abstract: During the last decade, the veterinary anesthetics have gained popularity as recreational drugs. The aim of this study was to document the use of "anestecia de caballo" (xylazine) and its consequences among drug users in Puerto Rico. The study combined a cross-sectional survey with 89 drug users and two focus groups conducted in Mayagüez with frontline drug treatment providers. Drug users were recruited from communities of the San Juan metropolitan area using a variety of ethnographic and outreach strategies. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(112 citation statements)
references
References 19 publications
2
94
2
1
Order By: Relevance
“…We often heard PWUD describe La Cura as a priority, an urgent matter— “ me tengo que curar (I have to cure myself).” At $3–5 per hit, they cured themselves an average of seven times per day – a figure reported by most of the syringe exchange clients we encountered in the field and consistent with the literature (Finlinson et al, 2006; Reyes et al, 2012). As consumers of adulterated narcotics, many Puerto Rican PWUD use Xylazine, in addition to or in lieu of heroin (Reyes et al, 2012; Torruella, 2011).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We often heard PWUD describe La Cura as a priority, an urgent matter— “ me tengo que curar (I have to cure myself).” At $3–5 per hit, they cured themselves an average of seven times per day – a figure reported by most of the syringe exchange clients we encountered in the field and consistent with the literature (Finlinson et al, 2006; Reyes et al, 2012). As consumers of adulterated narcotics, many Puerto Rican PWUD use Xylazine, in addition to or in lieu of heroin (Reyes et al, 2012; Torruella, 2011).…”
Section: Resultssupporting
confidence: 86%
“…As consumers of adulterated narcotics, many Puerto Rican PWUD use Xylazine, in addition to or in lieu of heroin (Reyes et al, 2012; Torruella, 2011). The Xylazine “cure” results in physical deterioration when the syringe injecting the drug ruptures the skin to penetrate the veins resulting in bodily lesions and subsequent scars (see Images 1-2).…”
Section: Resultsmentioning
confidence: 99%
“…Cases related to xylazine toxicity reported human plasma concentrations in a range among 1.0 µM and 20 µM [4, 52], these cases weren’t consider as drug users. The xylazine concentration on plasma users could be higher than these reported cases, considering that an epidemiologic study reported an increase in the frequency of injection since beginning to use xylazine (4–7/daily) [11, 12]. Which means, that xylazine concentrations used in this study are comparable, to the doses used by addicts.…”
Section: Discussionmentioning
confidence: 56%
“…In case of overdose, confusion, drowsiness, or transient loss of consciousness are documented. [2,3] In some case reports of xylazine poisoning, sedation, respiratory depression, bradycardia, hyperglycemia, and severe hypotension were observed. [2] It was also reported to be misused as a horse doping agent and as a drug of abuse.…”
Section: Introductionmentioning
confidence: 99%